A review on effect of plasma power density and gas flow rate on structural properties of nanocrystalline silicon - Tarjudin, Nurul Aini; Sumpono, Imam; Sakrani, Samsudi (Faculty of Science, Universiti Teknologi Malaysia, 2009)
Effects of plasma power density and gas density on structural properties of nanocrystalline silicon grown by Plasma Enhanced Chemical Vapor Deposition (PECVD)are discussed in this paper. It has been found that both gas flow rates and plasma power density have an opposite effect on the film’s crystallinity. It was observed that higher plasma power density tend to increase the degree of crystallinity, while higher gas flow rates appeared to decrease its curves. It was also observed that microstructural defects were lower for samples with lower crystallinity.